Employee testing: An ethical perspective - Davidson, Dan (Journal of business ethics, 1988)
This paper deals with the conflict between the desire of an employer to test employees for honesty and chemical dependency, and the right of the employee to privacy. Not only is the physical privacy of the employee infringed upon, but the psychic privacy of the individual as well. It is the conclusion of the paper that such an invasion of privacy is not justified without serious and compelling reason, and not the mere chance that testing will reveal problems among some percentage of the tested persons.